Perceptions of tourist transformations in the “Praça do Amor”, Parnaíba Brazil) - Costa, João Paulo Braga da; Fonseca, Ricardo (RITUR - Revista Iberoamericana de Turismo, 2025)
Spaces, as commodities, transform (and are transformed) as the environment in which they are inserted acquires new functions, for example urban and touristic. In this sense, the objective of the research was to identify the touristic transformations in Praça do Amor, in Parnaíba (Brazil). The qualitative and exploratory methodology considered a bibliographical review and field interviews with public managers, businesspeople, residents and tourists. The results showed that: the majority of the interviewees were from organized civil society, male, white and mixed race, with a high level of education; the square is considered an important attraction (more for tourism than leisure) of the city, is more recognized as a landscape than a space and contributes positively to the city, especially to the economy (especially Food and Beverage). It is concluded from the answers of the interviewees in comparison with the field observations and analysis of the satellite images that Praça do Amor was created as a public policy representing the private sector more than the community, although a sense of belonging on the part of the latter can be noted. Thus, it is believed that there is potential for the development of sustainable actions to transform it into a solid tourist product for the city, stimulating urban tourism and related segments.